Numerical Investigation of the Finite Thin Film Flow for Hybrid Nanofluid with Kerosene Oil as Base Fluid over a Stretching Surface along with the Viscous Dissipation and Variable Thermal Conductivity Effects - Yasir Mehmood; Ammar Alsinai; Ramsha Shafqat; Muhammad Bilal; Allah Yar Khan; Read S. A. Qahtan (Journal of Mathematics)
This study examines the flow and heat transfer of a finite thin layer of a hybrid nanofluid across an unstable stretching surface with varying thermal conductivity and viscous dissipation effects. A hybrid nanofluid model is considered to comprise two different types of nanoparticles, Go and Ag, with kerosene oil used as a base fluid. To study the phenomenon of thermal conduction, a modified version of Fourier’s law model is adopted because in the power-law model, the thermal conductivity depends on the velocity gradient. A system of nonlinear ordinary differential equations is obtained by considering the similarity transformations over the obtained rheological system of partial differential equations which is then tackled by a well-known numerical approach, i.e., the bvp4c MATLAB technique. The rheological impacts of the power-law index, solid volume fraction, film thickness, Eckert number, and modified Prandtl number on temperature and velocity fields are graphically discussed and illustrated. In the presence of nanoparticles, the temperature of the working fluid is enhanced and the power-law index has an inverse relation with the velocity of the hybrid nanofluid.